Effect of Notoginsenoside R1 on reparative dentin formation via regulating the function of human dental pulp stem cells - Xuan He; Dan Liang; Xinyi Zhao; Kaixin Liu; Zicheng Zhang; Meiling Li; Xuemeng Ma; Wenxia Chen; Xiaoyi Zhong (Tissue and Cell, 2027)

Exogenous dissolved organic matter redirects humic carbon fate at mineral interfaces through pre-contact molecular conditioning - Yu Li; Guangxu Mi; Jianghao Cheng; Meiling Zhang; Ying Liu; Shuang Ai; Fan Yang; Kui Cheng (Water Research, 2026)

Tricholoma matsutake polysaccharides promote physiological germination and metabolic reactivation of Bacillus cereus spores: Mechanisms and application in milk preservation - Meiling Zhao; Yujie Zhong; Yanjie Chen; Zhijia Liu; Chuanqi Chu; Qingyun Wang; Xiaoxia Zhao; Tao Wang; Junjie Yi (International Journal of Food Microbiology, 2026)

Oxygen-adaptive continuous lactate monitoring via dual-regime electrochemical sensing and dynamic calibration strategy - Xinyi Wang; Yuying Lin; Rubing Xiong; Jing Liu; Yue Liu; Zijie Li; Yongmei Chen; Yong Xia; Zhiqi Li; Lei Mou; Meiling Liu (Analytica Chimica Acta, 2026)

Comparative Lipidomics and microstructural characterization of Milk fat globule membrane protein powders from bovine buttermilk and cheese whey - Kuolin Si; Mengxueyao Zhang; Xuexing Zong; Yin Pei; Lu Liu; Xiuxiu Zhang; Meiling Ge; Xiaodong Li; Qingquan Yan (Food Research International, 2026)

Comparative transcriptomic insights into exopolysaccharide biosynthesis in Lactiplantibacillus plantarum induced by high-pressure processing and ultrasound: Enhanced yield, structural remodeling, and antioxidant capacity - Meiling Zhao; Jun Yuan; Yujie Zhong; Zhijia Liu; Chuanqi Chu; Junjie Yi; Tao Wang (Food Bioscience, 2026)

Zeolitic imidazolate framework enabled heat-resistant enzymatic biosensor for real-time and non-invasive detection of glucose - Qingwen Zhang; Meiling Yuan; Jingwen Chen; Ying Yang; Meng Lu; Chaoyue Cui; Xiaohu Liu; Hu Chen; Yi Wang (Chemical Engineering Journal, 2026)

Dietary compound probiotics enhance milk fat production, nutrient digestibility, and modulate hindgut health in lactating dairy cows - Danni Wei; Suran Liu; Meiling Zheng; Ming Deng; Baoli Sun; Yaokun Li; Guangbin Liu; Dewu Liu; Wenfeng Hu; Qingshen Liu; Yongqing Guo (Animal Feed Science and Technology, 2026)

Chemical reaction driven interfacial reconstruction of In2O3/S-BiOCl heterojunction with Ag2S quantum dots enables a self-validated fluorescence/photoelectrochemical dual mode nitrite sensing - Jingshu Li; Yuee Zhong; Manqi Li; Jiawei Zhou; Hengwen Tang; Jing Liu; Jianru Tang; Xiaohua Zhu; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2026)

Establishment of a reporter gene-based assay to determine ADCC activity of anti-tetanus toxin monoclonal antibody - Xiumei Jin; Bo Liu; Meiling Hu; Erqiang Wang; Huiyuan Gao; Zhe Lü (Toxicon, 2026)

Inhibition of methane production in an alpine wetland of the Tibetan plateau by carbon-based nanomaterials - Chengfang Ma; Rong Wen; Miao Lin; Hongfei Chi; Meiling Feng; Pengfei Liu (Environmental Research, 2026)

Forecasting transportation decarbonization pathways and deciphering structural moderating mechanisms in in-situ urbanization: An interpretable machine learning and multi-scenario assessment framework - Lu Chen; Wei Liu; Meiling Wu; Jingyi Zhao; Fanjie Luo (Environmental Impact Assessment Review, 2026)

Inner Ear Organoids: Recent Progress and Challenges - Yingxinyu Li; Cairong He; Jiayan Liu; Haiqin Zhang; Hongxia Zhang; Zheyu He; Mengyang He; Meiling Chen; Feiyan Zhou; Jie Ding (Stem Cell Reviews and Reports, 2026)

Landsat observation reveals upward trend of surface water temperature in the Three Gorges Reservoir over the past quarter century: divergent effects of climate changes and dam constructions - Han Peng; Botian Zhou; Dongmin Wang; Yue Yuan; Guang Li; Meiling Liu; Ling Wu; Mingsheng Shang (Journal of Oceanology and Limnology, 2026)

Uncovering the synergistic effects of digital–intelligent transformation and industrial structure upgrading on eco-efficiency:Evidence from 284 Chinese cities - Meiling Wu; Wei Liu; Rongguang Zhang; Yuying Yue (Journal of Cleaner Production, 2026)

Regional climate downscaling simulations for China since the Last Glacial Maximum - Naixin Cao; Liang Ning; Jian Liu; Zhengyu Liu; Mi Yan; Weiyi Sun; Meiling Jiang; Xueyuan Kuang; Huayu Lu; Kefan Chen; Yanmin Qin; Qin Wen; et al. (Science China Earth Sciences, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Spatiotemporal cube for identifying Cd-dominated heavy metal stress in rice using signal decomposition and hotspot analysis from GF-6 time series images - Yanan Wen; Tianyi Wang; Meiling Liu; Hui Zhang; Yuxin Zhao; Ben Yang; Xutao Yan; Ling Wu (International Journal of Remote Sensing, 2026)

Pseudomonas aeruginosa in Chinese mitten crab Eriocheir sinensis: Identification, pathogenic potential and control with Bdellovibrio powder - Li He; Yueqi Yang; Yiyao Liu; Meiling Liu; Haipeng Cao; Chunlei Gai; Weidong Ye (Journal of Invertebrate Pathology, 2026)

Linking molecular heterogeneity of artificial humic acid to divergent cadmium coordination behaviors - Yu Li; Xianghui Meng; Shuang Ai; Meiling Zhang; Guangxu Mi; Yurun Miao; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2026)

Effects of CaCl2 on the lipid properties of rapidly salted separated egg yolk and lipidomic analysis - Yaotong Liu; Meiling Xu; Yajie Chang; Shiwen Xu; Yujie Chi (Food Research International, 2026)

Bionic construction and performance assessment of 3D bioprinted small-diameter artificial blood vessels - Yuan-Zhu Xin; Wenyu Jin; Qianqian Wu; JunHee Lee; Geng Li; Yan Chen; Jun Liu; Seok-Jo Yang; Jiazi Gao; Meiling Quan; Zhenning Liu (Chemical Engineering Journal, 2026)

Bioinspired domed cone-pillar nanoarrays design for robust and low-haze-transparent superhydrophobic quartz glass - Yingying Dou; Yue Fan; Qiongwen Fu; Meiling Tao; Junyin Ouyang; Hongtao Liu; Lin Liu; Yabin Yang; Shilin Huang; Shan Zhou; Xuelin Tian (Chemical Engineering Journal, 2026)

Synergistic atomic-level anchoring and pore engineering of cobalt-nitrogen-carbon for anti-fouling and robust capacitive deionization - Huakun Pan; Haodong Zhang; Xinxi Teng; Yang Fan; Yaming Wang; Lin Li; Guisong Zhang; Meiling Liu; Haiou Song; Aimin Li; Shupeng Zhang (Chemical Engineering Journal, 2026)

Genome-wide analysis of the papaya bZIP gene family identifies CpbZIP52 as a key regulator of fruit postharvest ripening - Meiling Ding; Shanni Cao; Meng Zeng; Min Zhang; Hongya Tang; Xiaochun Chen; Xianqi Fu; Sicheng Bai; Min Yang; Kaidong Liu (Plant Science, 2026)

Effects of nodule geometry on collection performance and structural improvement of a rotary-rake collector for deep-sea mining - Qiang Yang; Zekun Chen; Junlan Deng; Meiling Liu; Jianxin Xia; Dingbang Wei (Ocean Engineering, 2026)

Dissolved organic matter dynamics and antibiotic resistance gene attenuation during composting: Characteristics and interrelationships - Dongfang Shi; Meiling Shi; Shengnan Zhang; Pengyan Zhang; Xiaoyan Qian; Yongjun You; Chong Liu; Fayong Li (Journal of Environmental Chemical Engineering, 2026)

Zwitterionic polyurethane-based solid polymer electrolytes for high-performance solid-state Lithium metal batteries - Jiaxing Liu; Bei Deng; Meiling Liu; Yaxue Zhang; Zhihao Yang; Tieqi Huang; Hongtao Liu (Chemical Engineering Journal, 2026)

Design and Performance Evaluation of Amino Acid-Decorated UiO-66-NH2/Pebax Mixed Matrix Membranes for Efficient CO2 Separation - Xiaochun Jing; Wei Zhao; Pengzhi Bei; Hongjing Liu; Yan Dai; Xu Zhao; Chengpeng Zhang; Meiling Shi; Ying Zhang (Water, Air, & Soil Pollution, 2026)

Impacts of vegetation management on pollination network structure and robustness in urban parks: A case study from Beijing Wenyu River Park - Yaxuan Li; Meiling Shu; Chenxi Li; Liwen Liu; Yan Zhou; Lan Wu; Yuyu Wang (Urban Ecosystems, 2026)

Drug-Induced Noninfectious Myocarditis/Pericarditis: A Real-World Pharmacovigilance Study Using the FAERS Database - Shijie Zhao; Weiyi Chen; Chao Tao; Ke Wang; Liuxuan Yang; Ruixiao Li; Meiling Zhou; Jinlu Shang; Xianbin Liu (Cardiovascular Toxicology, 2026)

SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

Decoupling predictors of arbuscular mycorrhizal fungal α- and β-diversity: Plant phylogeny versus functional traits in an alpine artificial grassland of Three-River Source Region - Guoxi Shi; Yingli Ma; Ning Wu; Meiling Guo; Xinchuang Wang; Yongjun Liu; Huyuan Feng; Huakun Zhou; Buqing Yao (Applied Soil Ecology, 2026)

Global distribution of the terrestrial moisture dynamics response to the meteorological dry-wet abrupt alternation - Jianyu Fu; Mingzhu Cao; Yang Lu; Chunzhu Wei; Xuejin Tan; Meiling Zheng; Liqian Peng; Wenhao Jia; Bingjun Liu (Journal of Hydrology, 2026)

Characteristics of the microbial carbon pump in kelp farming areas and the impact of artificial reefs: A metagenomic and ecological perspective - Junyang Ma; Jihua Liu; Zhansheng Guo; Meiling Zhu; Zitong Chai; Feng Jiang; Zhu Li; Zhenlin Liang; Zhaoyang Jiang (Environmental Research, 2026)

Interleukin-12 Supports Self-renewal Division of Mouse Hematopoietic Stem Cells in Polyvinyl Alcohol-Based Culture - Jinglei Zhai; Xialin Li; Meiling Yin; Sen Zhang; Xiaoming Liu; Lisha Wang; Nini Wang; Lin Wang; Hideo Ema; Fang Dong (Stem Cell Reviews and Reports, 2026)

Effects of different dark septate endophyte species on growth, Pb tolerance and associated physiological responses in Astragalus membranaceus under Pb stress - Gen Li; Meiling Wu; Qingqing Liu; Yashuo Tian; Simiao Wang; Yibang Zhang; Qing Dang; Fei Cao; Li Han (Plant and Soil, 2026)

Bidirectional gut-heart axis interactions in the context of predictive, preventive, and personalised medicine: a time-course analysis of comorbidity and mortality risk in a large population cohort - Meiling Cao; Di Liu; Haotian Wang; Cancan Li; Huapeng Lin; Lijuan Wu; Youxin Wang (EPMA Journal, 2026)

Effects of doped Mn on ferrihydrite transformation and the associated arsenic behavior during sulfidation-reoxidation process - Kun Gao; Xudong Bai; Meiling Yin; Shuai Wang; Xingxing Wang; Juan Liu; Zhi Dang (Journal of Hazardous Materials, 2026)

Community characteristics and risks of disinfection residual bacteria (DRB) during intermittent chlorination of stored rainwater - Zhiwen Chen; Xiaobin Liao; Binxiong Hu; Ye Yang; Meiling Liu; Yingying Dong; Tao Li; Likun Lv; Mawuli Dzakpasu; Yuefeng Xie; Wendong Wang (Journal of Environmental Chemical Engineering, 2026)

Valorization of saline byproducts: Development of composite films from waste salted egg white and plant extracts - Meiling Xu; Yajie Chang; Xuying Wang; Shiwen Xu; Yaotong Liu; Yanqu Ma (Food Research International, 2026)

Bridging data gaps in landslide early warning: Physics-derived rainfall thresholds under rainfall uncertainty - Hao Zou; Weiye Huang; Ting Liu; Henghao Cai; Shuai Mao; Bing Chen; Meiling Wu; Qingyu Zhang; Xiao Liu; Shu Zhang (Engineering Geology, 2026)

Pioneer Plants Improved the Suitability of Lead–Zinc Tailings for Plant Growth - He Gong; Xusheng Jiang; Hui Qiu; Luyang Wang; Meiling Zhang; Xinyue Teng; Jie Liu (Water, Air, & Soil Pollution, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Investigation of Oil Content in Lacustrine Shale-Oil Systems: Insights from Two Different Pyrolysis - Yuping Wu; Chenglin Liu; Fujie Jiang; Tao Hu; Chenxi Zhang; Jiahao Lyu; Renda Huang; Meiling Hu; Guanyun Wu; Rizwan Sarwar Awan (Journal of Earth Science, 2026)

Tracing thallium pollution in arsenic mining/smelting areas using high-precision thallium isotopic composition - Xudong Wei; Shunlong Jiang; Jin Wang; Hangfei Guo; Dieyu Chen; Ke Lin; Meiling Yin; Wanpeng Chen; Yinyin Lu; Yurong Gao; Juan Liu (Applied Geochemistry, 2026)

A bacteriohopanetetrol stereoisomer in Western Pacific oxycline indicates anammox-driven nitrogen loss and warm eddy dynamics - Liqin Duan; Jinming Song; Meiling Yin; Xiaowei Wang; Chuanyu Liu; Jiawei Kan; Zhuoyue Wang; Feng Zhao; Xuegang Li; Huamao Yuan (Geochimica et Cosmochimica Acta, 2026)

Iron single-atom/cluster nanozyme with enhanced oxidase-like activity for fluorescent/colorimetric analysis of Total antioxidant capacity in food - Meiling Chen; Yongmin Lei; Junlin Liu; Qiming Liu; Xingjian Song; Ting He; Guo-jun Zhang; Yujie Sun; Yulin Zhang; Yuqing Qin; Shaowei Chen (Food Chemistry, 2026)

Stability and Transport of Ferrihydrite Nanoparticles in Alkaline Soils - Yan Gong; Meiling Wang; Shuting Tian; Qingwei Ding; Xia Li; Gaiqiang Yang; Qi Liu; Juanfang Yang; Lijuan Huo (Water, Air, & Soil Pollution, 2026)

Bibliometric analysis of Pseudomonas aeruginosa vaccine development highlighting research status, evolution, and future opportunities - Shiqin Huang; Yi Zhou; Meiling Wu; Xinyan He; Jie Liu; Xinyao Chen; Chunyong Xia; Wen Wu; Ying Fan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nicking-controlled biosensor: Integrating DNA Walker-RCA circuit with trimetallic nanozyme for aflatoxin B1 detection - Longsheng Jin; YuJing Liu; Wenqing Xia; Meiling Zhou; Ziying Xiao; Jingyu Ge; Xiao Yuan; Qinqiang Zhu; Meisheng Wu (Analytica Chimica Acta, 2026)

Research on high-resolution PM2.5 concentration estimation methods based on transfer learning - Meiling Xing; Bo Li; Wenhao Zhang; Guohong Li; Xiufeng Yang; Qiyue Liu; Qichao Zhao (Advances in Space Research, 2026)

Metagenomic and metatranscriptomic characterization of syntrophic propionate- and butyrate-oxidizing bacterial communities in Qiangyong proglacial lake sediments on the Qinghai-Tibet Plateau - Rong Wen; Hongfei Chi; Meiling Feng; Yang Zhao; Chengfang Ma; Keshao Liu; Qi Yan; Pengfei Liu (Soil Ecology Letters, 2026)

Predicting ecological risks of heavy metals in watersheds based on interpretable machine learning models: under the framework of data scarcity - Hong Chen; Meiling Kong; Zhenghua Wu; Liu Gong; Lanlan Huang; Yihan Li; Fazhi Xie (Environmental Monitoring and Assessment, 2026)

Evaluation of the antibacterial and antioxidant potential of the endophytic fungus EFY14 from Cannabis sativa L. leaves through metabolomics and molecular docking - ShanShan Li; MeiLing Zhang; Ying Zhai; Yan Zhao; Ming Zhao; LiJie Liu; FeiYao Zhong; ZhiGang Wang; Shuai Li (Natural Product Research, 2026)

Impact of energy transition on pollution mitigation and carbon emission reduction - Meiling Wang; Zichen Liu (Environment, Development and Sustainability, 2026)

An Ultrasensitive 1,2,3-Triazole Schiff-Based Fluorescence Probe for the Detection of Al3+ and Developing Application of Biological Activity - Chunyang Liu; Junfeng Chen; Xun Kang; Meiling Le; Huajie J. Feng; Wenying Y. He (Journal of Fluorescence, 2026)

Seasonal gut microbiota and functional dynamics in brittle star (Ophiothrix exigua) from the Yellow Sea, China - Md. Tariful Islam Fuad; Yue Dong; Zhong Li; Meiling Ge; S.M. Sharifuzzaman; Xiaoshou Liu; Xuelei Zhang; Qinzeng Xu (Marine Environmental Research, 2026)

Spatiotemporal graph for detecting evolution characteristics of karst rocky desertification from long time-series Landsat images - Yanan Wen; Meiling Liu; Zeyan Wu; Qian Zhang; Jialei Su; Zijian Hu (CATENA, 2026)

Effectiveness and mechanism of in situ sludge biochar carrier enhancing salt-tolerant bacteria for pyrazolone degradation in high-salinity pharmaceutical wastewater - Yuying Ma; Zheyu Chen; Genping Yi; Ezzat H Elshazly; Qingshan Liu; Hongyan Zhang; Meiling Zheng; Aijie Wang; Wenzong Liu (Bioresource Technology, 2026)

Impact of Drought‐Flood Abrupt Alternation on Vegetation Productivity in Karst and Non‐Karst Regions of Southern China - Meiling Zheng; Jianyu Fu; Yan Jin; Yadong Ji; Shengkun Dong; Bingjun Liu (International Journal of Climatology, 2026)
Drought‐flood abrupt alternation (DFAA)—characterised by rapid transitions between drought and flood events—is an extreme compound natural hazard that threatens ecosystems, particularly in fragile environments such as karst regions. Soil moisture is a key indicator of surface hydrological processes, directly regulating vegetation growth and recovery. This study utilises the Standardised Soil Moisture Index (SSMI) to identify DFAA events and applies Granger causality analysis to reveal soil moisture‐vegetation interactions. The impact of DFAA on vegetation productivity is quantified, with a comparative analysis between karst and non‐karst regions in southern China. The results indicate that: (1) From 2000 to 2020, SSMI showed a significant upward trend. Drought‐to‐flood events were more frequent, intense, and longer in duration than flood‐to‐drought events. Both types of events also exhibited substantial spatial heterogeneity. (2) SSMI and NDVI were positively correlated, with the strongest correlation reaching 0.32 at a 60‐day lag. Bidirectional causality between SSMI and NDVI was predominant, affecting 49.24% of the study area. (3) Flood‐to‐drought events synergistically intensified drought–flood stress, whilst drought‐to‐flood events mitigated stress effects. Consequently, vegetation recovery was slower after flood‐to‐drought events, particularly in hydrologically vulnerable karst regions.

Unveiling the seasonal variations in greenhouse gas emissions from a representative full-scale swine farm’s wastewater treatment system via life cycle assessment - Xingyun Yuan; Meiling Lu; Zhiyin Wu; Zixuan Liu; Xin Wen; Baohua Ma; Yongde Zou; Tao Chen; Yinbao Wu (Process Safety and Environmental Protection, 2025)

Effects of long-term plastic film mulching on microplastic and phthalate esters pollution in salt-affected soils: Microbial community shifts and enrichment of putative degraders - Jiabin Li; Yunfeng Pu; Yongjun You; Shengnan Zhang; Xiaoyan Qian; Meiling Shi; Guocai Ma; Chong Liu; Kamel M. Eltohamy; Fayong Li (Journal of Hazardous Materials, 2025)

Solar-driven superhydrophobic modified polyurethane sponge for rapid in-situ recovery of oil and microplastics in marine oil spill co-contamination - Chuanliang Zhao; Sidan Peng; Bo Wu; Le Kang; Lanlan Liang; Meiling Liu; Liwei Yang; Wendong Wang; Xing Xu (Journal of Hazardous Materials, 2025)

Application of soda residue based material in a vertical flow constructed wetland for the simultaneous removal of tetracycline and phosphorus from freshwater aquaculture effluent - Ye Yang; Binxiong Hu; Tao Li; Meiling Liu; Ahmed Omer Abdalrahim Mohamed; Yingying Dong; Mawuli Dzakpasu; Hang Li; Yingyue Wang; Wendong Wang (Journal of Environmental Chemical Engineering, 2025)

Towards greenhouse gases mitigation for liquid pig slurry management with solid-liquid separation technologies - Wenhua Liao; Meiling Liu; Yuan Bian; Wenjing Wang; Zhiling Gao (Journal of Environmental Management, 2025)

Numerical simulation of wind field characteristics and enhanced heat exchange performance for the novel bucket-shaped anti-frosting evaporator - Guodong Qiu; Meiling Huang; Dan Liu; Yanfeng Chen; Weihua Cai (International Journal of Refrigeration, 2025)

Laser-engineered rattan evaporators for scalable and sustainable solar desalination - Haocheng Xu; Yingpeng Liu; Pei Qi Woon; Meiling Chen; Xinwu Xu; Bofan Li (Chemical Engineering Journal, 2025)

Multi-mechanism collaborative photocatalytic CH4 conversion over Cu/ZnS/ZnOx-550 Z-scheme heterojunction - Weixin Li; Qing Liu; Zhongxuan Yin; Yongqing Ma; Ganhong Zheng; Chuhong Zhu; Zhenxiang Dai; Meiling Wang (Chemical Engineering Journal, 2025)

Salt-induced amino acid metabolism enhances nutritional quality of alfalfa: evidence from metabolomic profiling - Liying Liu; Meiling Hou; Yinghao Liu; Duowen Sa; Qiang Lu; Boyi Qi (Plant and Soil, 2025)

Patterns and Influencing Mechanism of Plant Species Richness of Carex-dominated Wetlands in China - Jingci Meng; Guodong Wang; Yue Guo; Meiling Zhao; Nanlin Hu; Yusong Yuan; Yantong Zhao; Qi Chen; Zhibin Ren; Bo Liu; Ming Jiang (Chinese Geographical Science, 2025)

AKR1B1 is Required for Maintaining Acute Leukemia Cell Survival by Epigenetic Silencing of Tumor Suppressor Genes - Jingyu Chen; Lu Xu; Wangshi Li; Meiling Sun; Yao Chen; Ting Qiu; Yue Wu; Xingzhi Lv; Fukai Liu; Huitao Fan (Biochemical Genetics, 2025)

Impact of soil moisture depth variation on agricultural drought monitoring in karst and non-karst areas of southwest China: a case study of Yunnan Province - Meiling Zheng; Jianyu Fu; Yan Jin; Yadong Ji; Shengkun Dong; Bingjun Liu (CATENA, 2025)

Fast prediction of indoor temperature distribution under spatiotemporal variation of solar radiation using equivalent surface heat sources and multimodal CNN - Ye Yuan; Junxi Gao; Meiling Li; Gang Liu; Yuebo Yu; Zixuan Yu; Hanyuan Zhang (Building and Environment, 2025)

Sequential temperature design in high-speed railway stations: A dynamic thermal strategy balancing thermal comfort and energy efficiency - Ye Yuan; Meiling Li; Junxi Gao; Gang Liu; Zongwu Xu; Ying Chen; Hanyuan Zhang (Building and Environment, 2025)

Impacts of turbulent intermittency and pressure oscillation on persistent heavy haze pollution - Qianhui Li; Wei Wei; Hongsheng Zhang; Meiling Sun; Bingui Wu; Jingle Liu (Atmospheric Research, 2025)

Wheat yield prediction using an enhanced WOFOST with soil stratified hydrothermal module driven by GLASS and ERA5-land products over Yellow River Basin - Jing Zhang; Guijun Yang; Meiling Gao; Lijie Zhang; Weinan Chen; Miao Liu; Youming Zhang; Aohua Tang; Zhenhong Li (Computers and Electronics in Agriculture, 2025)

Hierarchically superhydrophobic ceramic fiber membrane with thermal-induced pore modulation for antifouling oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Huaiyuan Wang (Chemical Engineering Journal, 2025)

Bacteriochlorophyll reveals estuarine hypoxia and anoxygenic photosynthetic carbon fixation - Jiawei Kan; Liqin Duan; Jinming Song; Meiling Yin; Xuegang Li; Xiaoqi Liu; Huamao Yuan; Yingxia Wang (Limnology and Oceanography, 2025)
Bacteriochlorophylls (Bchls) are photosynthetic pigments produced by aerobic anoxygenic photosynthetic bacteria and anoxygenic photosynthetic bacteria. However, the sources, degradation, and influence of redox conditions in marine environments remain unclear. This study investigated the distribution of Bchls in the Changjiang Estuary to evaluate their origins, degradation, and environmental response. Results showed that total bacteriochlorophylls a (T Bchl a ), including bacteriochlorophyll a (Bchl a ) and its degradation product bacteriopheophytin a (Bphe a ), were higher in surface waters than in bottom waters in the inner estuary, where microbial evidence ( Sphingomonadaceae ) identified aerobic anoxygenic photosynthetic bacteria as the dominant source of T Bchl a . In contrast, the outer estuary exhibited elevated T Bchl a in bottom waters, with purple sulfur bacteria ( Chromatiaceae and Ectothiorhodospiraceae ) as the primary contributors. Significant negative correlations between Bphe a concentrations in bottom seawaters and surface sediments and the dissolved oxygen levels in bottom waters, along with a positive correlation between Bphe a in the surface sediments and the salinity difference between bottom and surface seawaters (Δ S ), suggest that Bphe a may serve as a useful indicator of hypoxia and water stratification. The contribution of anoxygenic photosynthetic bacteria to carbon fixation is expected to increase notably, potentially reaching 16% of phytoplankton carbon fixation after 100 years under expanding hypoxia. These findings establish Bchls as reliable indicators of hypoxia and water stratification and provide a framework for reevaluating carbon fixation in global hypoxic coastal systems.

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Robust cyclic olefin thermoplastic elastomer with excellent mechanical and thermal performance - Xiaohui Mao; Meiling Pu; Yuanbo Liu; Zhe Ma; Li Pan; Yuesheng Li (Chemical Engineering Journal, 2025)

Spatial distribution and risk assessment of microplastics in surface sediments in semi-enclosed waters: a case study of Laizhou Bay - Xuzhen Zhang; Hongxian Chu; Meiling Yin; Yadong Liu; Peng Chen; Qiangqiang Zhang; Xuejian Dai; Linghao Kong (Frontiers in Marine Science, 2025)
Marine ecosystems are the most important sinks for microplastics (MPs) from inland sources, and the input of large quantities of MPs into the oceans poses a serious threat to marine organisms and ecosystems. However, the characteristics of MPs contamination and its risk in semi-enclosed seas remain poorly understood. In this research, we conducted a comprehensive analysis and evaluation of the distribution patterns and ecological risks related to MPs found in the surface sediments of Laizhou Bay. We gathered surface sediments from various locations within the bay, which were then processed and analyzed to assess the MP content. According to the results, MPs in Laizhou Bay were widely distributed, with abundances ranging from 36–2125.5 items/g d.w. at different points, with an average of 534.7 items/g d.w. The MP forms were mainly fragments (61.91%) and particles (37.45%), with polyamide (PA) (32.73%), polyethylene terephthalate (PET) (12.42%), and polyurethane (PU) (10.81%) being the most dominant polymer types. MPs mainly originated from marine aquaculture, fishing, and domestic plastic waste; the contribution from marine activities was higher than that from land-based inputs, and their migration and dispersion were mainly affected by the hydrodynamics of water body exchange and intra-bay circulation. According to the pollution load index, the risk index of MPs in Laizhou Bay ranged from 1 to 7.68, indicating a low pollution level. However, the polymer risk index indicated that microplastic pollution in Laizhou Bay was at high risk, and PU and polyvinyl chloride were identified as the primary high-risk sources. This study systematically analyzed the composition, distribution, and multiple source characteristics of MPs in Laizhou Bay. The ecological risks associated with these MPs were assessed through the analysis of pollution load and polymer risk indices. This research offers a valuable dataset and a scientific foundation for understanding and managing MP pollution in semi-enclosed marine environments.

Large-scale mapping and uncertainty assessment of dominant tree species in southern China based on Sentinel-2 time series - Ben Yang; Yuxin Zhao; Junji Li; Meiling Liu; Lei Feng; Botian Zhou; Ling Wu (Journal of Environmental Management, 2025)

Respective contribution of varied reactive oxygen species formed in methane conversion over calcined ferric sulfate - Qing Liu; Weixin Li; Zhongxuan Yin; Yongqing Ma; Ganhong Zheng; Chuhong Zhu; Meiling Wang (Journal of Environmental Chemical Engineering, 2025)

Surface engineering of copper peroxide nanodots and Au nanozyme on porphyrin-based metal-organic frameworks induces cascade reactions for colorectal cancer treatment - Haoyu Chen; Rong Liu; Jiaxin Fu; Xiaohan Zhang; Xiaohua Zhu; Mingjie Wei; Feng Liu; Peng Yin; Haitao Li; Youyu Zhang; Meiling Liu; Juewen Liu (Chemical Engineering Journal, 2025)

Calcium isotope composition of the Gangdese continental arc deep crust and implications for making continental crust - Meiling Wang; Zaicong Wang; Liang Guo; Zongqi Zou; Fei Wu; Wei Dai; Jingliang Guo; Kang Chen; Lanping Feng; Haihong Chen; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2025)

Synergistic enhancement of ionic conductivity and mechanical strength of inorganic hydroxide exchange membranes via orientation engineering for water electrolysis - Qingjie Xi; Wei Wang; Ruixiang Guo; Chenyi Zhao; Xiaofen Liu; Xiaorui Jin; Yongan Yang; Kai-Ge Zhou; Meiling Wu (Chemical Engineering Journal, 2025)

Confining PMo12 in flexible nanocages for enhanced electrochemical energy storage - Yuanyuan Yan; Chongji Wang; Yuhang Chen; Cao Wu; Kezhuo Xie; Zhenyu Liu; Tianyuan Zhang; Weifeng Liu; Xuguang Liu; Tian Wang; Zhaofeng Chen; Shengbo Sang; et al. (Chemical Engineering Journal, 2025)

Oxygen-containing functional groups of biochars enhancing the oxygen release of CaO2 and the generation of free radicals - Qiang Hu; Junheng Zhang; Yadi Pan; Kuan Ding; Chaoyang Xu; Jinyu Hou; Wuxing Liu; Chanchana Thanachayanont; Thipjak Na Lampang; Meiling Chen; Shu Zhang (Process Safety and Environmental Protection, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Spatiotemporal impacts of scientific and technological innovation and industry chain resilience on ecological Efficiency: Evidence from 284 Chinese cities - Meiling Wu; Wei Liu; Rongguang Zhang; Zhiran Fan; Xueyan Zhong (Journal of Environmental Management, 2025)

Characteristics and mechanism of paclobutrazol degradation by the novel bacterial strain Kurthia gibsonii CGMCC 32305 - Wenxin Zhang; Meiling Shi; Yue Lou; Xinyi Liu; Xiaoli Dai; Yang Liu; Zhaoyu Li; Xu Su; Jiajia Li; YongQiang Tian (Journal of Environmental Chemical Engineering, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Rapid visual detection of glutathione in vegetables and distinguishing multiple sulfur-containing compounds by smartphone-assisted sensor based on calcined PPy@CuNi-ZIF-67 nanozyme with enhanced oxidase-like activity - Linchun Nie; Jiazhi Xia; Jiawei Liao; Na Liu; Meiling Xu; Dejing Meng; Wenjing Liu; Qingxiang Zhou; Chunmao Chen (Food Chemistry, 2025)

The design of novel lithium salt additives: 4-benzonitrile-1,3-double (trimethylboric acid) lithium (LBTA) to endow inherent superior stability in high voltage lithium ion batteries - Lucheng Li; Meiling Liu; Peng Yang; Wenfeng Yuan; Jun Chen (Chemical Engineering Journal, 2025)

Revealing the key organelle in the pathophysiology and clinical applications of animal toxins: Mitochondria - Linfeng Wang; Jiahao Liu; Sheng Zhou; Jiaqi Sun; Meiling Liu; Jianqi Zhao; Lixia Cheng; Zejing Wen; Xiaowen Bi; Chunhong Huang (Toxicon, 2025)

Sensitive measurement of polycyclic aromatic hydrocarbons based on strong enrichment from magnetic covalent organic framework before high performance liquid chromatography analysis - Guangyu Dong; Liushan Jiang; Linchun Nie; Jiawei Liao; Xiaodie Geng; Wenjing Liu; Dejing Meng; Meiling Xu; Na Liu; Qingxiang Zhou; Chunmao Chen (Journal of Environmental Chemical Engineering, 2025)

Deep Learning Imaging-Based Reconstruction Improved the Image Quality of Synthetic High B-Value DWI for Prostate Lesion Detecting - Xiuxiu Zhou; Hanxiao Zhang; Song Jiang; Jiankun Dai; Lingling Gu; Pei Zhang; Ye Fu; Jie Shi; Xinyi Wan; Meiling Xu; Shiyuan Liu; Li Fan (Journal of Medical and Biological Engineering, 2025)

A Hypothetical Protein Fragment from Large Yellow Croaker (Larimichthys crocea) Demonstrates Significant Activity Against Both Bacterial and Parasite - Chunmei Yan; Meiling Chen; Hao Xu; Jian Jin; Xiande Liu; Zhiyong Wang; Dongling Zhang (Fishes, 2025)
Antimicrobial peptides (AMPs) are biocompatible and biodegradable, making them an attractive alternative to traditional antimicrobial agents and chemical preservatives. Here, a novel α-helix amphiphilic anionic AMP Lc149 was screened from a large yellow croaker (Larimichthys crocea) using a Bacillus subtilis expression system. Lc149 is a hypothesized protein fragment not annotated in the genome of a large yellow croaker. Both extracellular protein and recombinant Lc149 (rLc149) exhibited significant killing effects against Gram-negative Escherichia coli and Vibrio harveyi. Scanning and transmission electron microscopy revealed that rLc149 had the ability to disrupt bacterial cell membranes, causing irregular cell morphology, severe cell membrane damage, cytoplasm agglutination, and intracellular content leakage. Confocal laser scanning microscopy and flow cytometry further confirmed bacterial cell destruction and mortality rates of over 80%. Gel retardation assays and SDS-PAGE electrophoresis showed that rLc149 was unable to bind to bacterial DNA, but did reduce bacterial protein contents. Additionally, rLc149 maintained antibacterial activity against E. coli and V. harveyi upon exposure to temperatures of 25–100 °C, UV radiation time of 0–60 min, pH levels of 3–12, and different proteases. Biosafety assays revealed low hemolytic toxicity to erythrocytes of large yellow croaker, rabbit, and shrimp, and low cytotoxicity to large yellow croaker kidney cells and HEK 293T cells. More deeply, rLc149 also possessed significant killing activity against parasites. Therefore, rLc149 can be considered an antibacterial and antiparasitic drug in fisheries.

Unraveling the effects of extreme heat conditions on urban heat environment: Insights from local climate zones and integrated temperature data - Bin Wang; Meiling Gao; Yumin Li; Zhenhong Li; Zhenjiang Liu; Xuesong Zhang; Ying Wen (Sustainable Cities and Society, 2025)

Dietary arabinogalactan modulates immunity and improves gut barrier in broilers via regulating metabolome and gut microbiome - Yafei Liu; Qingxiu Liu; Miaolin Ma; Jiatu Zhang; Meiling Liu; Rainer Mosenthin; Lihong Zhao; Shimeng Huang; Qiugang Ma (Carbohydrate Polymers, 2025)

Autophagy in skeletal muscle dysfunction of chronic obstructive pulmonary disease: implications, mechanisms, and perspectives - Xiaoyu Han; Peijun Li; Meiling Jiang; Yuanyuan Cao; Yingqi Wang; Linhong Jiang; Xiaodan Liu; Weibing Wu (Journal of Zhejiang University-SCIENCE B, 2025)

Keystone taxa drive the synchronous production of methane and refractory dissolved organic matter in inland waters - Xinjie Shi; Wanzhu Li; Baoli Wang; Na Liu; Xia Liang; Meiling Yang; Cong-Qiang Liu (Water Research, 2025)

Advanced treatment of coal to ethylene glycol industry wastewater by catalytic ozonation: Performance and mechanism - Yingying Dong; Lan Yang; Nan Zhang; Ningning Xiao; Yongxia Sun; Ye Yang; Meiling Liu; Zhiwen Chen; Jiangwei Wang; Wendong Wang (Journal of Water Process Engineering, 2025)

A new flocculant tannic acid for improving separation efficiency and lowering gas emissions from liquid and solid fractions of dairy slurry - Wenhua Liao; Yuan Bian; Chunjing Liu; Meiling Liu; Wenxu Liang; Zhiling Gao; Yanxia Gao; Jianzhi Xie (Journal of Cleaner Production, 2025)

Melatonin treatment maintains the quality properties and storability of carambola fruit by modulating energy metabolism - Ting Hu; Shaojie Zheng; Qingqing Liu; Meiling Li; Jingyuan Chen; Huili Zhang; Mengshi Lin; Hetong Lin; Yihui Chen (Food Chemistry, 2025)

Influence of calcium carbonate on ferrihydrite bio-transformation and associated arsenic mobilization/redistribution - Bowei Zhang; Meiling Yin; Kun Gao; Zhi Dang; Chongxuan Liu (Environmental Pollution, 2025)

Abnormal sensory processing cortex in insomnia disorder: a degree centrality study - Hui Wang; Haining Li; Ziyi Liu; Chiyin Li; Zhaoyao Luo; Wei Chen; Meiling Shang; Huiping Liu; Fatemeh Naderi Nejad; Yuanping Zhou; Ming Zhang; Yingxiang Sun (Brain Imaging and Behavior, 2025)

Hypoxia exacerbate the marine ecological risk of arsenic: By stimulating its migration and release at the sediment-water interface - Liqin Duan; Jinming Song; Meiling Yin; Xiaoqi Liu; Xue Liu; Xuegang Li; Huamao Yuan (Water Research, 2025)

Ultrastable Ti@Ir core-shell catalyst with low iridium loading for water electrolysis at industrial-level current density - Jiahao Yang; Zhaoping Shi; Yibo Wang; Hongxiang Wu; Jing Ni; Pengbo Wang; Meiling Xiao; Changpeng Liu; Wei Xing (Chemical Engineering Journal, 2025)

2D manganese-doped calcium carbonate nanosheets as activable MRI/US imaging Guided enhanced calcium influx for Boosted regulatory cell death - Mingya Tan; Linlin Huo; Jie Zeng; Shiqi Zhu; Jianfeng Bao; Mengke Fan; Jiangyang Li; Meiling Liu; Jiayi Zhao; Zhenghuan Zhao (Chemical Engineering Journal, 2025)

Longitudinal relationship between built environment and physical fitness in Chinese children and adolescents: Findings from the COHERENCE study - Jinghong Liang; Shan Huang; Wenwen Bao; Yingqi Pu; Meiling Liu; Xiuzhi Yang; Zhuowen Wu; Jiaqi Chen; Guanghui Dong; Yajun Chen (Building and Environment, 2025)

Current advances in human-induced pluripotent stem cell-based models and therapeutic approaches for congenital heart disease - Meiling Cao; Yanshan Liu; Ying Sun; Ruiyi Han; Hongkun Jiang (Molecular and Cellular Biochemistry, 2025)

Dual-mode detection of human immunoglobulin via copper oxide nanozyme catalysis fluorescent species generation and photoelectrochemical alteration in ZnIn2S4/SnO2-based system - Jiawei Zhou; Lili Zhao; Yuee Zhong; Peipei Li; Xiaohua Zhu; Shu Huang; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2025)

Biotic and Abiotic Drivers of Ecosystem Temporal Stability in Herbaceous Wetlands in China - Guodong Wang; Nanlin Hu; Yann Hautier; Beth Middleton; Ming Wang; Meiling Zhao; Jingci Meng; Zijun Ma; Bo Liu; Yanjie Liu; Ming Jiang (Global Change Biology, 2025)
Maintaining the stability of ecosystems is critical for supporting essential ecosystem services over time. However, our understanding of the contribution of the diverse biotic and abiotic factors to this stability in wetlands remains limited. Here, we combined data from a field vegetation survey of 725 herbaceous wetland sites in China with remote sensing information from the Enhanced Vegetation Index (EVI) from 2010 to 2020 to explore the contribution of biotic and abiotic factors to the temporal stability of primary productivity. We found that plant species richness directly contributed to stability on a national scale, but that this contribution differed among climate zones, hydrological regimes, and vegetation types. In addition, many abiotic factors, including soil properties, geographical location, and climate also contributed to stability. Piecewise structural equation modeling identified that soil properties, including soil pH, total nitrogen, and soil organic carbon, emerged as primary factors modulating ecosystem stability, both directly and indirectly by affecting species richness and vegetation type. Higher species richness and soil organic carbon were related to higher ecosystem stability in peatlands but less so in coastal and inland marshes. These findings enhance our ability to forecast how wetland ecosystems may respond to future environmental changes and biodiversity loss and can inform policy decisions related to ecosystem stability.

Bacillus subtilis 2118 exhibits bactericidal activity due to an inserted fish cDNA library - Chunmei Yan; Meiling Chen; Jian Jin; Xiande Liu; Zhiyong Wang; Yongju Luo; Dongling Zhang (Aquaculture, 2024)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Paleoenvironmental evolution and East Asian monsoon records through three stages of paleochannels since the mid-pleistocene in the Western Bohai Sea, North China - Shuyu Wu; Jun Liu; Hongxian Chu; Yongcai Feng; Meiling Yin; Lixin Pei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Preparation of hydrophilic pulp cellulose-based membrane and its performance in oil-water separation - Qing Liu; Guorui Li; Kehui Qi; Huihui Zhang; Meiling Pu; Lu Li; Yanju Lu (Journal of Water Process Engineering, 2024)

Visible-light-assisted peroxymonosulfate activation using MIL-88A(Fe)/BiOI heterojunction composite to drive charge transport for eliminating acid red 18 - Meiling Wang; Xiaochun Liu; Kebin Li; Wenting Huo; Hong Wei; Hongna Zhang; Nannan Zhong; Hai-Ying Jiang (Journal of Environmental Chemical Engineering, 2024)

Functionalization of cellulose by facile Dissolution-Regeneration in A novel CS2/DBU/DMSO solvent system for detection of metal ions and antibacterial - Yuyan Zheng; Zinan Li; Meiling Chen; Jiyang Zuo; Tao Yang; Wenhua Miao; Yadong Zhao; Fei Liu; Jinggang Wang; Jin Zhu (Chemical Engineering Journal, 2024)

Genome Mining Analysis Uncovers the Previously Unknown Biosynthetic Capacity for Secondary Metabolites in Verrucomicrobia - Xue Di; Peng Li; Jingxuan Wang; Vincent Nowak; Shuai Zhi; Meiling Jin; Liwei Liu; Shan He (Marine Biotechnology, 2024)

Long Transients May be Temporary Visits of Concealed Alternative Stable States - Xudong Liu; Meiling Liu; Ruiqing Zhu; Changming Zhao; Ning Chen (Ecosystems, 2024)

Comparative karyotype analysis provides cytogenetic evidence for the origin of sweetpotato - Jianying Sun; Qian Zhang; Meiling Xu; Mengxiao Yan; Xingyu Liu; Jian Sun; Qinghe Cao; Hongxia Wang; Jun Yang; Zongyun Li; Yonghua Han (Chromosome Research, 2024)

Microbial inoculants using spent mushroom substrates as carriers improve soil multifunctionality and plant growth by changing soil microbial community structure - Hui Nie; Chong Li; Zhaohui Jia; Xuefei Cheng; Xin Liu; Qianqian Liu; Meiling Chen; Yong Ding; Jinchi Zhang (Journal of Environmental Management, 2024)

Genomic selection on ear height, plant height and grain yield in the primary testing stage of maize hybrids - Xinying Kong; Shuwen Ji; Yubo Liu; Xuecai Zhang; Meiling Liu; Chen Yue; Ruichen Yang; Cong Li; Xiaomei Dong; Ao Zhang; Yanye Ruan (Euphytica, 2024)

A novel and convenient lying cow identification method based on YOLOX and CowbodyNet: A study with applications in a barn - Jianxing Xiao; Yongsheng Si; Meiling Xie; Gang Liu; Zhang Yan; Kejian Wang (Computers and Electronics in Agriculture, 2024)

New perspective for pathomechanism and clinical applications of animal toxins: Programmed cell death - Jiaqi Sun; Jiahao Liu; Meiling Liu; Xiaowen Bi; Chunhong Huang (Toxicon, 2024)

Interfacial charge demulsification endowed dual-network photocatalytic hydrogen-bonded PVA@agarose membranes for oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Liyan Liu; Huaiyuan Wang (Journal of Hazardous Materials, 2024)

Development of multi-cross-linking, rapid curing, and easy cleaning, edible hydrogels for meat preservation - Yuxin Cheng; Jiaxin Xu; Rongfan Zhang; Jianguo Lin; Meiling Zhou; Xianmin Qin; Keshan Wang; Ying Zhou; Qiujin Zhu; Yongguo Jin; Yuanyuan Liu (Food Hydrocolloids, 2024)

Integrated effect of aspect ratio and tree spacing on pedestrian thermal comfort of street canyon - Xiaoping Chen; Meng Han; Jinyu He; Hang Ma; Meiling Han; Yanhong Liu; Xiaogang Wu (International Journal of Biometeorology, 2024)

Microbial regulation on refractory dissolved organic matter in inland waters - Wanzhu Li; Baoli Wang; Na Liu; Xinjie Shi; Meiling Yang; Cong-Qiang Liu (Water Research, 2024)

Biochar decreases cadmium uptake in indica and japonica rice (Oryza sativa L.): Roles of soil properties, iron plaque, cadmium transporter genes and rhizobacteria - Meiling Xu; Meiling Ren; Yu Yao; Qi Liu; Jing Che; Xiaozhi Wang; Qiao Xu (Journal of Hazardous Materials, 2024)

Synergistic enhancement of cadmium immobilization and soil fertility through biochar and artificial humic acid-assisted microbial-induced calcium carbonate precipitation - Yu Li; Meiling Zhang; Xiaobin Wang; Shuang Ai; Xianghui Meng; Zhuqing Liu; Fan Yang; Kui Cheng (Journal of Hazardous Materials, 2024)

Coupled physicochemical dual-crosslinking Ti3C2T composite aerogels for the selective adsorption of gallium ions in acid fly ash leaching - Xiaopei Zhang; Weifeng Liu; Chang Liang; Dongju Fu; Meiling Wang; Xuguang Liu (Journal of Hazardous Materials, 2024)

Progress in electrolyte regulation to enhance nitrogen reduction reaction - Qin Li; Xuguang Liu; Meiling Wang (Chemical Engineering Journal, 2024)

Phosphorylation of RasGRP1 by Shc3 prevents RasGRP1 degradation and contributes to Ras/c-Jun activation in hepatocellular carcinoma - Xinran Zhang; Yun Liu; Rui Yang; Yuanyuan Guo; Meiling Yan; Ying Xiao; Yunzhuo Dong; Ruixia Zhang; Yinpeng Qin; Yishan Bu; Yi Zhang; Huier Gao (Molecular and Cellular Biochemistry, 2024)

Three nona-2,7-dienoic acid derivatives from saltern derived Micromonospora sp. FXY415 - Meiling Wang; Zhonghui Zheng; Zhiyu Hu; Binbin Fan; Jiexi Liu; Qingyan Xu (Natural Product Research, 2024)

Dynamic response of sloping seabed with buried twin pipelines under wave loading - Fan Meiling; Duan Lunliang; Zhou Jianting; Liu Zhuang; Wang Duoyin (Ocean Engineering, 2024)

2,3-pyridinedicarboxylic acid-modified MIL-88A(Fe) for enhanced peroxymonosulfate activation to degrade organic contaminants - Meiling Wang; Xiaochun Liu; Kebin Li; Wenting Huo; Hong Wei; Hai-Ying Jiang (Journal of Water Process Engineering, 2024)

Spatiotemporal variations of plankton communities in different water bodies of the Yellow River: Structural characteristics, biogeographic patterns, environmental responses, and community assembly - Meiling Yi; Lingqi Li; Haoran Li; Chang Liu; Ya Deng; Zi Wu; Yang Li (Journal of Hydrology, 2024)

Effects of microplastics on sedimentary greenhouse gas emissions and underlying microbiome-mediated mechanisms: A comparison of sediments from distinct altitudes - Meiling Yi; Jingnan Liu; Maosen Ma; Sibo Zhang; Xin Chen; Xinghui Xia; Yang Li (Journal of Hazardous Materials, 2024)

Adsorption Performance of Chitosan and Glutaraldehyde Modified Biochars for Trivalent Antimony in Acidic Wastewater - Huifang Lei; Nora F. Y. Tam; Xinhua Geng; Meiling Zhong; Xiaolan Lao; Xiaotong Su; Xuexia Huang; Lezhang Wei; Yu Liu; Qihang Wu; Ying-heng Fei; Dinggui Luo; et al. (Water, Air, & Soil Pollution, 2024)

A new method of alkalinity remediation for Cd-contaminated groundwater by PAAS-modified MgCO3/Mg(OH)2 colloid - Bowen Li; Meiling Tang; Peng Wang; Shibin Liu; Meng Yao; Jun Dong (Chemosphere, 2024)

Cellulose nanofibrils-stabilized food-grade Pickering emulsions: Clarifying surface charge's contribution and advancing stabilization mechanism understanding - Yadong Zhao; Feifan Zhang; Meiling Chen; Fei Liu; Bin Zheng; Wenhua Miao; Huimin Gao; Rusen Zhou (Food Hydrocolloids, 2024)

Sheep dung deposition disrupted the soil microbiome in degraded grassland but not in non-degraded grassland - Yinghao Liu; Liying Liu; Meiling Hou (Environmental Research, 2024)

MXene-based composite aerogels with bifunctional ferrous ions for the efficient degradation of phenol from wastewater - Gaoyuan Li; Weifeng Liu; Shaojun Gao; Huayu Lu; Dongju Fu; Meiling Wang; Xuguang Liu (Chemosphere, 2024)

Histological and single-nucleus transcriptome analyses reveal the specialized functions of ligular sclerenchyma cells and key regulators of leaf angle in maize - Qibin Wang; Qiuyue Guo; Qingbiao Shi; Hengjia Yang; Meiling Liu; Yani Niu; Shuxuan Quan; Di Xu; Xiaofeng Chen; Laiyi Li; Wenchang Xu; Fanying Kong; et al. (Molecular Plant, 2024)

Novel superhydrophobic sponge with flower-like architecture for oily emulsion separation and organic pollutants photodegradation - Jinyue Yang; Zhanjian Liu; Jing Jing; Xiguang Zhang; Yuxin Fu; Meiling Li; Huaiyuan Wang (Journal of Environmental Chemical Engineering, 2024)

Subchronic co-exposure of polystyrene nanoplastics and 3-BHA significantly aggravated the reproductive toxicity of ovaries and uterus in female mice - Guanghua Xiong; Haiyan Zhang; Yulin Peng; Huangqi Shi; Meiling Han; Tianle Hu; Hongcheng Wang; Shangrong Zhang; Xiaoqing Wu; Gaoxiao Xu; Jun'e Zhang; Yong Liu (Environmental Pollution, 2024)

Correction to: Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)

Characteristics of splenic PD-1+ γδT cells in Plasmodium yoelii nigeriensis infection - Dianhui Chen; Feng Mo; Meiling Liu; Lin Liu; Junmin Xing; Wei Xiao; Yumei Gong; Shanni Tang; Zhengrong Tan; Guikuan Liang; Hongyan Xie; Jun Huang; et al. (Immunologic Research, 2024)
Although the functions of programmed death-1 (PD-1) on αβ T cells have been extensively reported, a role for PD-1 in regulating γδT cell function is only beginning to emerge. Here, we investigated the phenotypic and functional characteristics of PD-1-expressing γδT cells, and the molecular mechanism was also explored in the Plasmodium yoelii nigeriensis ( P. yoelii NSM)-infected mice . Flow cytometry and single-cell RNA sequencing (scRNA-seq) were performed. An inverse agonist of RORα, SR3335, was used to investigate the role of RORα in regulating PD-1 + γδT cells. The results indicated that γδT cells continuously upregulated PD-1 expression during the infection period. Higher levels of CD94, IL-10, CX3CR1, and CD107a; and lower levels of CD25, CD69, and CD127 were found in PD-1 + γδT cells from infected mice than in PD-1 − γδT cells. Furthermore, GO enrichment analysis revealed that the marker genes in PD-1 + γδT cells were involved in autophagy and processes utilizing autophagic mechanisms. ScRNA-seq results showed that RORα was increased significantly in PD-1 + γδT cells. GSEA identified that RORα was mainly involved in the regulation of I-kappaB kinase/NF-κB signaling and the positive regulation of cytokine production. Consistent with this, PD-1-expressing γδT cells upregulated RORα following Plasmodium yoelii infection. Additionally, in vitro studies revealed that higher levels of p-p65 were found in PD-1 + γδT cells after treatment with a RORα selective synthetic inhibitor. Collectively, these data suggest that RORα-mediated attenuation of NF-κB signaling may be fundamental for PD-1-expressing γδT cells to modulate host immune responses in the spleen of Plasmodium yoelii nigeriensis –infected C57BL/6 mice, and it requires further investigation.

STAT2 negatively regulates RIG-I in the antiviral innate immunity of black carp - Ji Liu; Chushan Dai; Lijun Yin; Xiao Yang; Jun Yan; Meiling Liu; Hui Wu; Jun Xiao; Weiguang Kong; Zhen Xu; Hao Feng (Fish & Shellfish Immunology, 2024)

Preparation, characterization and in vitro digestion of jujube polysaccharide microcapsules - Qingyi Li; Meiling Liu; Mengjun Liu; Huiqiang Wang; Zhihui Zhao (Food and Bioproducts Processing, 2024)

Enhanced reversible hydrogen storage in LiBH4-Mg(BH4)2 composite with V2C-Mxene - Qingbo Zhang; Jiaguang Zheng; Ao Xia; Meiling Lv; Zhenxuan Ma; Meijia Liu (Chemical Engineering Journal, 2024)

The short-term effect of simulated acid rain and nitrogen deposition on the soil microbial functional profile targeting C, N, and P cycling - Chong Li; Yong Ding; Shuifeng Zhang; Meiling Chen; Yuhao Wang; Zhaohui Jia; Shilin Ma; Jinchi Zhang; Xin Liu (Applied Soil Ecology, 2024)

Microbial features with uranium pollution in artificial reservoir sediments at different depths under drought stress - Siyu Liu; Juan Liu; Jingye She; Zhenyu Xie; Lei Zhou; Qunwei Dai; Xing Zhang; Yuebing Wan; Meiling Yin; Xinjiao Dong; Min Zhao; Diyun Chen; et al. (Science of The Total Environment, 2024)

Source appointment of δ13C in sediments of a maar lake in southern China: Implications of fossil fuel CO2 emissions - Meiling Guo; Yongming Han; Weiguo Liu; Yunning Cao; Dewen Lei; Weijian Zhou; Zhisheng An (Applied Geochemistry, 2024)

Pt,P-codoped carbon nitride nanoenzymes for fluorescence and colorimetric dual-mode detection of cholesterol - Meiling Chen; Yang Yang; Qinhua Chen; Lina Tang; Junlin Liu; Yujie Sun; Qiming Liu; Yulin Zhang; Guo-jun Zhang; Shaowei Chen (Analytica Chimica Acta, 2024)

Minocycline attenuates the bilirubin-induced developmental neurotoxicity through the regulation of innate immunity and oxidative stress in zebrafish embryos - Guanghua Xiong; Tianle Hu; Yihong Yang; Haiyan Zhang; Meiling Han; Jiahao Wang; Yipeng Jing; Hongbo Liu; Xinjun Liao; Yong Liu (Toxicology and Applied Pharmacology, 2024)

Stepwise degradation of organic matters driven by microbial interactions in China΄s coastal wetlands: Evidence from carbon isotope analysis - Meiling Yang; Na Liu; Baoli Wang; Yajun Li; Wanzhu Li; Xinjie Shi; Xinrui Yue; Cong-Qiang Liu (Water Research, 2024)

Using low-protein diet in egg production for win-win of productivity and environmental benefits should be prudent: Evidence from pilot test - Meiling Liu; Shunju Geng; Qingfeng Wang; Jinqiu Mi; Lihong Zhao; Jianyun Zhang; Cheng Ji; Hongliang Wang; Qiugang Ma; Shimeng Huang (Science of The Total Environment, 2024)

Anaerobic granular sludge performance in an expanded granular sludge bed reactor treating calcium-rich wastewater by adjusting CaCO3 crystallization: Effect of upflow velocity and Ca2+ concentration - Xiaoji Liu; Dongning Pan; Quan Yuan; Xiyuan Feng; Meixuan Li; Xuening Song; Meiling Li; Yajuan Ge; Yukun Xing; Yuanzhou Yu; Zhengyu Jin (Science of The Total Environment, 2024)

Calcium isotopic compositions of eclogite melts and negligible modification during reaction with lithospheric mantle - Zongqi Zou; Zaicong Wang; Xiao-Jun Wang; Yi-Gang Xu; Li-Hui Chen; Meiling Wang; Lanping Feng; Ming Li; Yongsheng Liu (Geochimica et Cosmochimica Acta, 2024)

Identification of QTLs associated with very-long chain fatty acid (VLCFA) content via linkage mapping and BSA-seq in peanut - Xiaomeng Xue; Jianguo Li; Jie Wu; Meiling Hu; Nian Liu; Liying Yan; Yuning Chen; Xin Wang; Yanping Kang; Zhihui Wang; Huifang Jiang; Yong Lei; et al. (Theoretical and Applied Genetics, 2024)

Migration and transformation of soil phosphorus by organic acids: a global meta-analysis - Ying Zhao; Meiling Zhang; Zhuqing Liu; Fan Yang (Journal of Soils and Sediments, 2024)

In situ formation of fluorescence species for the detection of alkaline phosphatase and organophosphorus pesticide via the ascorbate oxidase mimetic activity of AgPd bimetallic nanoflowers - Luo Luo; Jing Liu; Yani Liu; Haoyu Chen; Youyu Zhang; Meiling Liu; Shouzhuo Yao (Food Chemistry, 2024)

One-step synthesis of color-tunable carbon dots-based organic long persistent luminescence materials - Yujie Di; Weifeng Liu; Shuhao Shi; Tao Wu; Meiling Wang; Xuguang Liu (Chemical Engineering Journal, 2024)

Silver nanowire-infused carbon aerogel: A multifunctional nanocellulose-derived material for personal thermal management - Meiling Zhang; Yinan Fan; Ni Wang; Hongguo Gao; Lei Zhang; Yanjiao Zhao; Lifang Liu (Carbohydrate Polymers, 2024)

Black carp LGP2 suppresses RIG-I mediated IFN signaling during the antiviral innate immunity - Yixuan He; Ji Liu; Yujia Miao; Meiling Liu; Hui Wu; Jun Xiao; Hao Feng (Fish & Shellfish Immunology, 2023)

Dual responsive cellulose-based fluorescent material fabricated in a CO2 switchable solvent for multifunctional applications - Yiting Xu; Xiaobo Yu; Meiling Chen; Yi Sun; Wei Zhang; Yajin Fang; Lanyun Fang; Haining Na; Fei Liu; Jin Zhu (Chemical Engineering Journal, 2023)

Scalable fabrication of a robust asymmetric superwetting Janus mesh by facile spray-coating for oil–water emulsions separation - Jing Jing; Zhanjian Liu; Xiguang Zhang; Jinyue Yang; Meiling Li; Ruixia Yuan; Guolin Jing; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Bilobetin attenuates Staphylococcus aureus virulence by targeting Von Willebrand factor-binding protein and staphylocoagulase - Chongling Zhang; Wenyuan Zhang; Shuyue Zhu; Chunjie Hu; Sihua Che; Meiling Wang; Mengli Jin; Nan Bian; Wu Song; Shuang Jiang; Yijing Jiang; Juan Hou; et al. (World Journal of Microbiology and Biotechnology, 2023)

A halogen-free hyper-crosslinked ionic polymer for efficient multi-conversion of CO2 into carbonates under mild conditions, with a combination of theoretical study - Bowen Jiang; Jia Liu; Wenjie Xiong; Meiling Weng; Jigang An; Yuewei Fan; Leizhi Zheng; Guoqiang Yang; Zhibing Zhang (Chemical Engineering Journal, 2023)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Intrinsic photothermal phase change materials with enhanced toughness and flexibility for thermal management in extreme environments - Meiling Cui; Chong Tian; Yunyun Yang; Lei Huang; Qiang Liu; Na Yang; Fuqi Zhao; Xufu Cai; Weibo Kong (Chemical Engineering Journal, 2023)

Thermo-responsive ion imprinted polymer on the surface of magnetic carbon nanospheres for recognizing and capturing low-concentration lithium ion - Chang Liang; Xiaopei Zhang; Weifeng Liu; Xingfu Song; Shuying Sun; Dongju Fu; Geng Dong; Meiling Wang; Yonghui Bai; Xuguang Liu (Minerals Engineering, 2023)

Designing a cercosporin-bioinspired bifunctional algicide with flocculation and photocatalysis for efficiently controlling harmful cyanobacterial blooms - Zhenbo Yuan; Meiling Liu; Zengping Su; Huibin Xu; Changmei Liu; Liushen Lu; Lingling Wang; Xiaonan Zhu; Yan Zhang; Yijian Rao (Journal of Hazardous Materials, 2023)

Structure regulation of two-dimensional composites facilitates solar/electric desalination - Xiaoran Cheng; Chenyang Xing; Weifeng Liu; Meiling Wang; Xuguang Liu; Jiadong Zhou (Chemical Engineering Journal, 2023)

Metabolic profiling of Apostichopus japonicus body wall exposed to a typical type of PBDEs: potential health risks and impact on sea cucumber health - Kui Ding; Pengji Zhuo; Meiling Ge; Xiaomei Liao; Jing Mo; Shilin Liu; Qinzeng Xu; Xuelei Zhang (Frontiers in Marine Science, 2023)
Introduction Sea cucumbers are cultivated mainly for their valuable body wall. Polybrominated diphenyl ethers are common persistent pollutants in sea waters with known impacts on aquatic animals nonetheless not yet studied for the body wall of sea cucumbers. Methods Using ltra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Triple-TOF-MS), we investigated the metabolic impact of 2,2',4,4'-tetrabromodiphenyl ether (BDE-47) on the body wall of Apostichopus japonicus . etabolite changes and metabolic pathway alterations were assessed in response to three distinct concentrations of BDE-47: 0.1 µg/L, 1.0 µg/L, and 10.0 µg/L. REsults Exposure to BDE-47 led to notable alterations in the metabolic profiles of the body wall. A total of 95~102 metabolites in the 0.1 ~ 10.0 µg/L BDE-47 treated group were altered significantly, and various disrupted metabolic pathways were identified and characterized. These metabolites and metabolic pathways were mainly involved in lipid metabolism, energy metabolism, immunity, oxidative stress, inflammation, and neurotoxicity. Discussion The findings of our study shed light on the potential health risks that polybrominated diphenyl ethers present to sea cucumbers. This underscores the imperative for both researchers and policymakers to delve deeper into further investigations and studies. These results indicate the necessity for enhanced monitoring and management practices within the sea cucumber aquaculture industry to mitigate the impact of these persistent organic pollutants and protect the health and safety of this valuable resource.

Exploring the repairing mechanisms of reduced graphene oxide (rGo) on the dysregulation of Xenopus Laevis larva hypothalamus-pituitary-thyroid (HPT) axis caused by chiral triazole fungicide metconazole - Yue Deng; Meiling Zheng; Rui Liu; Haixia Zeng; Jingling Diao; Ran Xiao; Xiaoxuan Su (Pesticide Biochemistry and Physiology, 2023)

Development and evaluation of diffusive gradients in thin-films technique with a novel titanium peroxide binding gel for in situ measurement of Tl in natural waters and sediments - Hongmei Deng; Meiling Liu; Zhaodong Liu; Minhua Su; Yue Gao; Danxing Yang; Yuxuan Liu; Liang Ma; Zhiqiang Yu; Tangfu Xiao; Jun Luo (Journal of Hazardous Materials, 2023)

Analysis of seismic escape accessibility and risk in old community with unreinforced masonry buildings - Meiling Xiao; Jianbin Xie; Cuilin Liu; Haiyan Zhu; Yong Zhu; Yujie Fu; Jun Ren (Stochastic Environmental Research and Risk Assessment, 2023)

Fine genetic mapping confers a major gene controlling leaf shape variation in watermelon - Ming Xu; Meiling Gao; Sikandar Amanullah; Yu Guo; Xiuping Bao; Yaru Duan; Xiujie Liu; Jixiu Liu; Yue Gao; Feishi Luan (Euphytica, 2023)

Oil occurrence state and quantity in alkaline lacustrine shale using a high-frequency NMR technique - Chenxi Zhang; Fujie Jiang; Tao Hu; Di Chen; Liliang Huang; Zhenxue Jiang; Xiaohao Wang; Zheyu Liu; Yuping Wu; Jiahao Lv; Renda Huang; Meiling Hu; et al. (Marine and Petroleum Geology, 2023)

Development and Characterization of Multifunctional Wound Dressing with the Property of Anti-bacteria and Angiogenesis - Xi He; Meiling Zhou; Xuemei Chen; Jing Wang; Xiaoli Zhao; Yanxia Zhu; Tao Liu (Probiotics and Antimicrobial Proteins, 2023)

Ag2S QDs integration with MnO2 nanosheets for the sensitive detection of Cr (VI) via the redox reaction induced photoelectrochemical variation - Lili Zhao; Haoyu Chen; Ying Tang; Peipei Li; Xiaohua Zhu; Jingyi Liu; Meiling Liu; Youyu Zhang; Shouzhuo Yao (Analytica Chimica Acta, 2023)

The positive effects of mineral-solubilizing microbial inoculants on asymbiotic nitrogen fixation of abandoned mine soils are driven by keystone phylotype - Chong Li; Zhaohui Jia; Shuifeng Zhang; Tao Li; Shilin Ma; Xuefei Cheng; Meiling Chen; Hui Nie; Lu Zhai; Bo Zhang; Xin Liu; Jinchi Zhang; et al. (Science of The Total Environment, 2023)

Characterisation of kapok fibre's biochar for arsenate adsorption removal from aqueous solution. - Kanfolo Franck Herve Yeo; Yingying Dong; Tongxuan Xue; Zhiwen Chen; Nan Zhang; Ye Yang; Liu Han; Meiling Liu; Ange Nsilani Kouediatouka; Hanse Pablick Patherny Lobo Mouguegue; Wendong Wang (Environmental Research, 2023)

Atomically dispersed metal catalysts towards nitrogen reduction for Ammonia: From homogeneous to heterogeneous - Di Yang; Jinsheng Li; Meiling Xiao; Changpeng Liu; Wei Xing; Jianbing Zhu (Chemical Engineering Journal, 2023)

Application of interaction models in predicting the simultaneous growth of Staphylococcus aureus and different concentrations of background microbiota in Chinese-style braised beef - Chuansong Cheng; Binxiong Liu; Meiling Tian; Ting Fang; Changcheng Li (Meat Science, 2023)

Lacticaseibacillus casei LH23 Suppressed HPV Gene Expression and Inhibited Cervical Cancer Cells - Shiyue Hu; Yunpeng Hao; Xiao Zhang; Yaping Yang; Meiling Liu; Nan Wang; Tong-Cun Zhang; Hongpeng He (Probiotics and Antimicrobial Proteins, 2023)

Response of microbial communities to nutrient removal in coastal sediment by using ecological concrete - Meiling Zhang; Jiannan Ji; Lemian Liu; Yisong Guo; Jianfeng Chen (Environmental Science and Pollution Research, 2023)

Target and non-target analysis of organochlorine pesticides and their transformation products in an agrochemical-contaminated area - Di Huang; Lirong Gao; Shuai Zhu; Lin Qiao; Yang Liu; Qiaofeng Ai; Chi Xu; Wenwen Wang; Meiling Lu; Minghui Zheng (Chemosphere, 2023)

Catalytic destruction of chlorobenzene over K-OMS-2: Inhibition of high toxic byproducts via phosphate modification - Yunpeng Long; Jiajia Liu; Meiling Chen; Renna Li; Xiaole Weng; Zhongbiao Wu (Journal of Environmental Sciences, 2023)

Subducted carbonates not required: Deep mantle melting explains stable Ca isotopes in kimberlite magmas - Michael A. Antonelli; Andrea Giuliani; Zaicong Wang; Meiling Wang; Lian Zhou; Lanping Feng; Ming Li; Zhaofeng Zhang; Fang Liu; Russell N. Drysdale (Geochimica et Cosmochimica Acta, 2023)

Evidence Supporting That C-to-U RNA Editing Is the Major Force That Drives SARS-CoV-2 Evolution - Jinxiang Wang; Liqun Wu; Xiaoxin Pu; Baoyi Liu; Meiling Cao (Journal of Molecular Evolution, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Negatively regulation of MAVS-mediated antiviral innate immune response by E3 ligase RNF5 in black carp - Jun Yan; Guoxia Qiao; Enhui Wang; Yuqing Peng; Jiamin Yu; Hui Wu; Meiling Liu; Jiagang Tu; Yongan Zhang; Hao Feng (Fish & Shellfish Immunology, 2023)

Long-term effect of intermediate particulate matter (PM1–2.5) on incident asthma among middle-aged and elderly adults: A national population-based longitudinal study - Shuting Li; Jing Wei; Yaoyu Hu; Yuhong Liu; Meiling Hu; Yadi Shi; Yongxi Xue; Mengmeng Liu; Wenhan Xie; Xiuhua Guo; Xiangtong Liu (Science of The Total Environment, 2023)

Self-intercepting interference of hydrogen-bond induced flexible hybrid film to facilitate lithium extraction - Meiling Wang; Tianyuan Zhang; Zhixiang Meng; Chongji Wang; Weikang Dong; Jijian Liu; Su Yang; Xudong Hou; Xiaoran Cheng; Weifeng Liu; Chenyang Xing; Xuguang Liu; et al. (Chemical Engineering Journal, 2023)

Cellulose-based fluorescent materials fabricated in CO2 switchable solvent for freshness monitoring - Yi Sun; Wei Zhang; Shan Lu; Wenhua Miao; Meiling Chen; Fei Liu; Haining Na; Jin Zhu (Carbohydrate Polymers, 2023)

High-throughput sequencing reveals tuber mustard genes responsive to Plasmodiophora brassicae in the early stage of infection - Zhaoming Cai; Meiqin Xiang; Jing Tan; Chunhong Cheng; Ying Liu; Jiayu Shi; Meiling Shi; Jin Li; Diandong Wang (Physiological and Molecular Plant Pathology, 2023)

Partial substitution of manure reduces nitrous oxide emission with maintained yield in a winter wheat crop - Huizhou Gao; Yajing Xi; Xueping Wu; Xuexia Pei; Guopeng Liang; Ju Bai; Xiaojun Song; Meiling Zhang; Xiaotong Liu; Zixuan Han; Gang Zhao; Shengping Li (Journal of Environmental Management, 2023)

Long-term effect of submicronic particulate matter (PM1) and intermodal particulate matter (PM1-2.5) on incident dyslipidemia in China: A nationwide 5-year cohort study - Meiling Hu; Jing Wei; Yaoyu Hu; Xiuhua Guo; Zhiwei Li; Yuhong Liu; Shuting Li; Yongxi Xue; Yuan Li; Mengmeng Liu; Lei Wang; Xiangtong Liu (Environmental Research, 2023)

A highly-stretchable and adhesive hydrogel for noninvasive joint wound closure driven by hydrogen bonds - Hongsheng Liu; Xiaole Hu; Wen Li; Meiling Zhu; Jinhuan Tian; Lihua Li; Binghong Luo; Changren Zhou; Lu Lu (Chemical Engineering Journal, 2023)

Eco-friendly waterborne superhydrophobic/superoleophilic FEVE composite coating with prolonged mechanochemical and anti-scaling properties - Zhanjian Liu; Lina Ren; Baoshuang Zhang; Jing Jing; Xiguang Zhang; Meiling Li; Yuxin Fu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Comprehensive transcriptome analysis unravels the crucial genes during adventitious root development induced by carbon monoxide in Cucumis sativus L. - Fahong Yun; Dengjing Huang; Meiling Zhang; Chunlei Wang; Yuzheng Deng; Rong Gao; Xuemei Hou; Zesheng Liu; Weibiao Liao (Molecular Biology Reports, 2022)

Plant Growth Regulators Enhance Saline–Alkali Tolerance by Upregulating the Levels of Antioxidants and Osmolytes in Soybean Seedlings - Minglong Yu; Qiong Wu; Dianfeng Zheng; Naijie Feng; Xilong Liang; Meiling Liu; Yao Li; Baomin Mou (Journal of Plant Growth Regulation, 2022)

Molecular mapping of candidate gene regulating fruit stripe trait in watermelon - Xiaoxue Liang; Meiling Gao; Sikandar Amanullah; Yu Guo; Hongguo Xu; Xiaosong Liu; Xiujie Liu; Jixiu Liu; Yue Gao; Chengzhi Yuan; Xuezheng Wang; Feishi Luan (Euphytica, 2022)

How soil salinization and alkalinization drive vegetation change in salt-affected inland wetlands - Yantong Zhao; Guodong Wang; Meiling Zhao; Ming Wang; Bo Liu; Ming Jiang (Plant and Soil, 2022)

Research progress on antidiabetic activity of apigenin derivatives - Jingyi Jiang; Ting Tang; Yaling Peng; Meiling Liu; Qianwen Liu; Pengbing Mi; Zehua Yang; Hongfei Chen; Xing Zheng (Medicinal Chemistry Research, 2022)

The Sponge Interaction Between Circular RNA and microRNA Serves as a Fast-Evolving Mechanism That Suppresses Non-small Cell Lung Cancer (NSCLC) in Humans - Liqun Wu; Meiling Cao; Xiaoxin Pu; Baoyi Liu; Jinxiang Wang (Journal of Molecular Evolution, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Antibacterial Activities of Peptide HF-18 Against Helicobacter pylori and its Virulence Protein CagA - Chenyu Zhou; Meiling Jiang; Xinyue Ye; Xiaoyun Liu; Wenxuan Zhao; Lingman Ma; Changlin Zhou (International Journal of Peptide Research and Therapeutics, 2022)

Bentazone in water and human urine in Wuhan, central China: exposure assessment - Pei Wang; Meiling Cao; Feng Pan; Junling Liu; Yanjian Wan; Huaiji Wang; Wei Xia (Environmental Science and Pollution Research, 2022)

Implications of spatial priority areas for hydrological ecosystem services through coupling hydrology model and Zonation model under different economic costs of water utilizations in northernmost of Japan - Min Fan; Manjiang Shi; Yunfeng Liu; Wen Chen; Yue Deng; Meiling Wang (Mitigation and Adaptation Strategies for Global Change, 2022)

Analyzing the micro-pore characteristics of tight oil reservoirs through the implementation of mercury intrusion technique - Meiling Jiang; Yunfeng Zhang; Yang Liu (Arabian Journal of Geosciences, 2021)

Pigment profile and gene analysis revealed the reasons of petal color difference of crabapples - Ting Shen; Meiling Han; Qianrui Liu; Chen Yang; Jiaxin Meng; Houhua Li (Brazilian Journal of Botany, 2021)

Study of the lower limit of pore throat filling in tight sandstone reservoir of Gaotaizi oil layer in Qijia area - Meiling Jiang; Yunfeng Zhang; Yang Liu (Arabian Journal of Geosciences, 2021)

The Effect of Composting on the Multiple Heavy Metals in the River Sediment Investigated by Multivariate Analysis - Yaoning Chen; Yanrong Chen; Yuanping Li; Yihuan Liu; Daoli Zhang; Yanxin Wu; Hui Li; Fangting Xu; Meiling Li (Water, Air, & Soil Pollution, 2021)

Functional wastepaper-montmorillonite composite aerogel for Cd2+ adsorption - Yaoning Chen; Yihuan Liu; Yuanping Li; Li Zhao; Yanrong Chen; Hui Li; Yuqing Liu; Linshenzhang Li; Fangting Xu; Meiling Li (Environmental Science and Pollution Research, 2020)

Viral aetiology and clinical characteristics of acute respiratory tract infections in Shenzhen during epidemic of coronavirus disease 2019 - Dawei Zhang; Yong Jiang; Jianjiang Hua; Qiong Liu; Wujin Wen; Meiling Zhu; Jikun Du; Helu Liu (Infectious Diseases, 2020)

Genetic basis of maize ear angle revealed by high-density single nucleotide polymorphism markers in four recombinant inbred line populations - Jingwei Lin; Shoukun Li; Gengyuan Liang; Meiling Liu; Taicheng Jin; Zhengwei Qu; Haoge Li; Shuisen Chen; Cong Li; Ao Zhang; Yanye Ruan; Zhenhai Cui (Euphytica, 2020)

Connectivity of fish assemblages along the mangrove-seagrass-coral reef continuum in Wenchang, China - Jianguo Du; Meiling Xie; Yuyu Wang; Zehao Chen; Wenhua Liu; Jianji Liao; Bin Chen (Acta Oceanologica Sinica, 2020)

Genetic architecture of fruit size and shape variation in cucurbits: a comparative perspective - Yupeng Pan; Yuhui Wang; Cecilia McGregor; Shi Liu; Feishi Luan; Meiling Gao; Yiqun Weng (Theoretical and Applied Genetics, 2020)

Two new monoterpene glucosides from Xanthium strumarium subsp. sibiricum with their anti-inflammatory activity - Hai Jiang; Xudong Xing; Meiling Yan; Xinyue Guo; Lin Yang; Liu Yang (Natural Product Research, 2019)

Genetic Structure and Diversity of Glycyrrhiza Populations Based on Transcriptome SSR Markers - Yaling Liu; Yaping Geng; Meiling Song; Pengfei Zhang; Junling Hou; Wenquan Wang (Plant Molecular Biology Reporter, 2019)

Investigation of Lactic Acid Bacteria Isolated from Giant Panda Feces for Potential Probiotics In Vitro - Qian Liu; Xueqin Ni; Qiang Wang; Zhirong Peng; Lili Niu; Meiling Xie; Yicen Lin; Yi Zhou; Hao Sun; Kangcheng Pan; Bo Jing; Dong Zeng (Probiotics and Antimicrobial Proteins, 2019)

Genetic characterization of a new astrovirus in goslings suffering from gout - Meiling Jin; Xiaoyan Wang; Kang Ning; Ning Liu; Dabing Zhang (Archives of Virology, 2018)

Response of the groundwater system in the Guanzhong Basin (central China) to climate change and human activities - Wenke Wang; Zaiyong Zhang; Lei Duan; Zhoufeng Wang; Yaqian Zhao; Qian Zhang; Meiling Dai; Huizhong Liu; Xiaoyan Zheng; Yibo Sun (Hydrogeology Journal, 2018)

Important interaction of chemicals, microbial biomass and dissolved substrates in the diel hysteresis loop of soil heterotrophic respiration - Qing Wang; Nianpeng He; Yuan Liu; Meiling Li; Li Xu; Xuhui Zhou (Plant and Soil, 2018)

Long noncoding RNAs in the mTOR signaling network: biomarkers and therapeutic targets - Tinglei Huang; Meiling Wang; Bo Huang; Augustus Chang; Feng Liu; Yanjie Zhang; Bin Jiang (Apoptosis, 2018)

Characterization of a novel dsRNA mycovirus isolated from strain A105 of Rhizoctonia solani AG-1 IA - Meiling Zhang; Li Zheng; Chen Liu; Canwei Shu; Erxun Zhou (Archives of Virology, 2018)

Development of Fluorescence-Linked Immunosorbent Assay for Icariin - Jinjun Cheng; Yan Zhao; Meiling Zhang; Yue Zhang; Xiaoman Liu; Xin Yan; Yongzhi Wang; Ziwei Sun; Qingguo Wang; Huihua Qu (Journal of Fluorescence, 2017)

Molecular cloning and expression analysis of major intrinsic protein gene in Chlamydomonas sp. ICE-L from Antarctica - Lulu Li; Meiling An; Changfeng Qu; Zhou Zheng; Yibin Wang; Fangming Liu; Yingying He; Xiaodong He; Jinlai Miao (Extremophiles, 2017)

A glucuronokinase gene in Arabidopsis, AtGlcAK, is involved in drought tolerance by modulating sugar metabolism - Wenjun Xiao; Shuai Hu; Xiaoxun Zhou; Runyu Yao; Jingru Luo; Congying Yuan; Hongping Chang; Cheng Zhang; Ji Huang; Jinyan Li; Shucan Liu; Meiling Li; et al. (Plant Molecular Biology Reporter, 2017)

Structure and geochronology of the Tongbai complex and their implications for the evolution of the Tongbai orogenic belt, central China - Huan Liu; Shoufa Lin; Chuanzhong Song; Meiling Wu (International Geology Review, 2017)

Round fruit shape in WI7239 cucumber is controlled by two interacting quantitative trait loci with one putatively encoding a tomato SUN homolog - Yupeng Pan; Xinjing Liang; Meiling Gao; Hanqiang Liu; Huanwen Meng; Yiqun Weng; Zhihui Cheng (Theoretical and Applied Genetics, 2017)

Characterization of BcMF23a and BcMF23b, two putative pectin methylesterase genes related to pollen development in Brassica campestris ssp. chinensis - Sue Lin; Li Huang; Xiaolin Yu; Xingpeng Xiong; Xiaoyan Yue; Tingting Liu; Ying Liang; Meiling Lv; Jiashu Cao (Molecular Biology Reports, 2017)

Accumulation of intact sulfur mustard in adipose tissue and toxicokinetics by chemical conversion and isotope-dilution liquid chromatography–tandem mass spectrometry - Bin Xu; Cheng Zong; Yajiao Zhang; Tianhong Zhang; Xiaoying Wang; Meiling Qi; Jianfeng Wu; Lei Guo; Peng Wang; Jia Chen; Qin Liu; Hua Xu; et al. (Archives of Toxicology, 2017)

Biomass, nutrient uptake and fatty acid composition of Chlamydomonas sp. ICE-L in response to different nitrogen sources - Meiling An; Yibin Wang; Fangming Liu; Xiaoqing Qi; Zhou Zheng; Naihao Ye; Chengjun Sun; Jinlai Miao (Acta Oceanologica Sinica, 2017)

Abnormal Functional Connectivity Density in Post-traumatic Stress Disorder - Youxue Zhang; Bing Xie; Heng Chen; Meiling Li; Feng Liu; Huafu Chen (Brain Topography, 2016)

Dissecting the complex molecular evolution and expression of polygalacturonase gene family in Brassica rapa ssp. chinensis - Ying Liang; Youjian Yu; Xiuping Shen; Heng Dong; Meiling Lyu; Liai Xu; Zhiming Ma; Tingting Liu; Jiashu Cao (Plant Molecular Biology, 2015)

Integrating Genome-Wide Association Study and Brain Expression Data Highlights Cell Adhesion Molecules and Purine Metabolism in Alzheimer’s Disease - Zimin Xiang; Meiling Xu; Mingzhi Liao; Yongshuai Jiang; Qinghua Jiang; Rennan Feng; Liangcai Zhang; Guoda Ma; Guangyu Wang; Zugen Chen; Bin Zhao; Tiansheng Sun; et al. (Molecular Neurobiology, 2015)

Characterization of Post-traumatic Stress Disorder Using Resting-State fMRI with a Multi-level Parametric Classification Approach - Feng Liu; Bing Xie; Yifeng Wang; Wenbin Guo; Jean-Paul Fouche; Zhiliang Long; Wenqin Wang; Heng Chen; Meiling Li; Xujun Duan; Jiang Zhang; Mingguo Qiu; et al. (Brain Topography, 2015)

Amyloid Beta-Derived Diffusible Ligands (ADDLs) Induce Abnormal Expression of Insulin Receptors in Rat Hippocampal Neurons - Xin Liu; Zongyan Teng; Can Cui; Ruitao Wang; Meiling Liu; Yina Zhang (Journal of Molecular Neuroscience, 2014)

Structure, Evolution, and Expression of the β-Galactosidase Gene Family in Brassica campestris ssp. chinensis - Jinlong Liu; Minghui Gao; Meiling Lv; Jiashu Cao (Plant Molecular Biology Reporter, 2013)

The complete genomic sequence of a novel mycovirus from Rhizoctonia solani AG-1 IA strain B275 - Li Zheng; Huiquan Liu; Meiling Zhang; Xiong Cao; Erxun Zhou (Archives of Virology, 2013)

Resveratrol protects against arsenic trioxide-induced nephrotoxicity by facilitating arsenic metabolism and decreasing oxidative stress - Meiling Yu; Jiangdong Xue; Yijing Li; Weiqian Zhang; Dexing Ma; Lian Liu; Zhigang Zhang (Archives of Toxicology, 2013)

In vitro evaluation of a mammary gland specific expression vector encoding recombinant human lysozyme for development of transgenic dairy goat embryos - Tao Gui; Meiling Zhang; Jianwen Chen; Yuanliang Zhang; Naru Zhou; Yu Zhang; Jia Tao; Liucai Sui; Yunsheng Li; Ya Liu; Xiaorong Zhang; Yunhai Zhang (Biotechnology Letters, 2012)

Effect of trichostatin A and 5-Aza-2′-deoxycytidine on transgene reactivation and epigenetic modification in transgenic pig fibroblast cells - Qingran Kong; Meiling Wu; Zhenkun Wang; Xinmiao Zhang; Lu Li; Xiangyu Liu; Yanshuang Mu; Zhonghua Liu (Molecular and Cellular Biochemistry, 2011)

Factors regulating trophic status in a large subtropical reservoir, China - Yaoyang Xu; Qinghua Cai; Xinqin Han; Meiling Shao; Ruiqiu Liu (Environmental Monitoring and Assessment, 2010)

Composition and variability of airborne fungi in an enclosed rabbit house in China - Zengmin Miao; Tongjie Chai; Chunhua Qi; Yumei Cai; Jingbo Liu; Wen Yuan; Meiling Yao (Aerobiologia, 2010)

Long-term cultured callus and the effect factor of high-frequency plantlet regeneration and somatic embryogenesis maintenance in Zoysia japonica - Li Liu; Xiaoli Fan; Junwei Zhang; Meiling Yan; Manzhu Bao (In Vitro Cellular & Developmental Biology - Plant, 2009)